1968
DOI: 10.1103/physrev.175.1350
|View full text |Cite
|
Sign up to set email alerts
|

Shell Model in the Continuum—Application to the Four-Nucleon System

Abstract: The continuum shell model is applied to the study of the elastic scattering of protons from He 3 as well as to the photodisintegration of He 4 . A semiquantitative fit is obtained for the scattering phases and the photoabsorption cross section using a model Hamiltonian consisting of a real, local potential and a finiterange effective interaction. Two approximations for the total wave function of the system are studied, and it is found that the photoabsorption cross section is sensitive to the approximation use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This procedure is shown to be indispensable, in order to avoid the appearance of spurious resonances in the region of excitation energies of interest. The parameters of the calculations have been essentially fixed in earlier studies [7,29] on negativeparity states. The only quantities that had to be specified here were the one-body potentials U, corresponding to the s-and d-waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is shown to be indispensable, in order to avoid the appearance of spurious resonances in the region of excitation energies of interest. The parameters of the calculations have been essentially fixed in earlier studies [7,29] on negativeparity states. The only quantities that had to be specified here were the one-body potentials U, corresponding to the s-and d-waves.…”
Section: Discussionmentioning
confidence: 99%
“…These can be broadly classified into three categories: (i) the R-matrix approach [1][2][3][4][5]; (ii) the resonating group method [6], which has been extensively applied to interpret the scattering of nucleons by the mass-3 system; and finally, (iii) the shell model in the continuum approach [7,8]. A systematic study of the negativeparity resonances by using the coupled-channels method based on the lp-i h model in the continuum [9] has shown that this formalism is quite successful in handling the nuclear structure and continuum aspects in a consistent and straightforward manner.…”
Section: Introductionmentioning
confidence: 99%